On the Equational Base of SMB Algebras - Petar Đapić; Sara Bačević; Fedor Kovačević (Mathematics, 2023)
The “semilattices of Mal’cev blocks”, for short SMB algebras, were defined by A. Bulatov. In a recently accepted paper by P. Đapić, P. Marković, R. McKenzie, and A. Prokić, the class of all SMB algebras and its subclass of regular SMB algebras were proved to be varieties of algebras. In this paper, we find an equational base of the first variety and simplify the previously known equational base of the second variety.